2022
DOI: 10.1007/s00405-022-07374-y
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on intratympanic drug delivery for Menière’s disease

Abstract: Purpose Intratympanic (IT) drug delivery receives attention due to its effectivity in treatment for Menière’s disease (MD). Due to the release of the consensuses and new evidence on IT drug delivery for MD have been published, the review with a view to supplementing the details of IT treatment of MD is indispensable. Methods The literatures on IT injection for MD treatment over the last two decades are retrieved, International consensus (ICON) on treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This fluctuation occurring only in ITG group and not in ITC group in our study is still harder to explain. We can only speculate that the ITC group as suggested by the prior pathogenesis plays a hearing protective role, which the ITG group lacks [ 14 , 22 , 32 ]. There has also been increased discussion in the last years suggesting that ITG might be more effective in controlling vertigo episodes than ITC with negligible hearing loss when used in low doses [ 6 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This fluctuation occurring only in ITG group and not in ITC group in our study is still harder to explain. We can only speculate that the ITC group as suggested by the prior pathogenesis plays a hearing protective role, which the ITG group lacks [ 14 , 22 , 32 ]. There has also been increased discussion in the last years suggesting that ITG might be more effective in controlling vertigo episodes than ITC with negligible hearing loss when used in low doses [ 6 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Much effort is being dedicated to optimize drug delivery through the intratympanic administration of hydrogels and nanoparticles. Intratympanic drug delivery has already been used in humans for intractable Menière's disease [62], for idiopathic sudden hearing loss [63,64], and recently, for cisplatin-induced ototoxicity [65,66]. The last studies have demonstrated that intratympanic injection of thiosulfate is feasible and safe, but the number of patients was very small, and more work is necessary to establish whether and in which conditions (such as time of injection relative to cisplatin infusion) it is possible to obtain otoprotection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of consensus statements and clinical practice guidelines from the USA, Europe, and China recommends the use of methylprednisolone over dexamethasone for intratympanic steroid administration. Within this review by Li et al [9 ▪ ] in 2022, an intratympanic gentamicin titration protocol is proposed that includes two injections 2 weeks apart with an end-point of vertigo cessation and/or unilateral vestibular loss on objective testing. When comparing intratympanic steroids versus gentamicin, a recent metanalysis by Lee et al (2021) [10] shows similar vertigo control rates, with better hearing outcomes for the steroid group.…”
Section: Updates In Medical Managementmentioning
confidence: 99%